PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK SEJARAH BERBASIS PERJUANGAN RADEN INTA I UNTUK MENINGKATKAN NILAI-NILAI NASIONALISME SISWA DI SMA NEGERI 1 TANJUNG RAYA - Iswandoyo, Beny; Musadad, Akhmad Arif; Sariyatun, S. (Sebelas Maret University (UNS), 2014)
Background: Learning media have an important functions in learning process, especially on historical subject. As a given of instructional media information could be help teachers overcome the problem of material that was difficult to explain verbally. Therefore, in this study of developed historical of instructional media that could be to increase a variety of media as well as supported the activities of historical teachers in the classroom. These products of this development are graphic media like a comic book. The historical of the comic media based on Raden Intan I struggle to increase the values of nationalism students’. This research aimed to find out: (1) to know using media on historical subject at SMA Negeri 1 Tanjung Raya; (2) to know process of development comic instructional media based Raden Intan I struggle at SMA N 1 Tanjung Raya; (3) to determine the effectiveness of using comic media historical based on Raden Intan I struggle to increase students’ nationalism.Methods: This study was a research and development one referring to Research and Development method (R&D) by using Borg and Gorl, and Sugiyono. This hypothetical model adopted Molenda’s ADDIE model, the procedure of this research are, preliminary studies, the development of instructional media, and test the effectiveness of instructional media. Analysis of feasibility test using Likert scale with 5 ranges and effectiveness test of instructional media using t-test. Conclusion: Based on the result of pretest and posttest experimental class, it could be found that 8.569 at significance level of 0.000>0.05, therefore could be said that any influence toward of using media. Effectiveness of nationalism the results using t test, which means that the value of 4.257 at significance of 0.000>0.05. It meant that the result of experiment class before and after treatment had unequal. Such the historical of comic based on struggle Raden Intan I on instructional media have more effective for improving students’ achievement and nationalism. Based on the results that show the experimental class have better than control class.